Implementation of Multi-Objective Optimisation Method On The Basis Of Ratio Analysis for Finalist Selection of Putra Putri Kampus Bengkulu Province - Kurnianto, Ridho Rahman; Hermansyah, Edy; Yupianti, Yupianti (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The Executive Board of the Campus Putra Putri Association (IPPK) of Bengkulu Province has utilised computers in the data processing process both registration data and assessment data. The implementation of the Multi-Objective Optimization Method On The Basis Of Ratio Analysis in the selection of finalists for the Putra Putri Kampus of Bengkulu Province was built using the PHP programming language with a MySQL database which can be accessed online via the link https://ppkbengkulu.online/. The implementation of the Multi-Objective Optimisation On The Basis Of Ratio Analysis method can simplify the data management process and provide information in the form of recommendations for the selection of finalists for the campus princess in Bengkulu Province. Based on tests that have been carried out using sample data from the registration of the 2024 campus princess son participants as many as 40 participants divided into 20 boys and 20 girls, the results of recommendations through the Moora Method are the best 15 boys and the best 15 girls as the Finalists of the Putra Putri Kampus Bengkulu Province. Based on the results of Black Box testing, it shows that the application functions properly and is able to recommend the best finalists for the Putra Putri Kampus Bengkulu Province Selection using the Multi-Objective Optimization On The Basis Of Ratio Analysis Method.